Analisis Penempatan Pegawai Pengalih Media Menjadi Fungsional Pustakawan Pada Unit Kerja Alih Media Perpustakaan Nasional Republik Indonesia - Leni Sudiarti; Retna Purwaningsih; Tri Indah Susilowati; Zeni Aniroh; Ratna Johari Pamungkas; Hamka (Jurnal IPI (Ikatan Pustakawan Indonesia), 2022)
availability of librarians should be considered considering the high workload, required a number of qualified and competent librarians. This study uses a descriptive method with a qualitative approach by conducting literature reviews and interviews with loci at the National Library of the Republic of Indonesia. The purpose of the study was to find out how the process of placing employees in the media transfer unit is, by adjusting the workload analysis (position requirements) and placements that take into account the knowledge, abilities, and attitudes needed. Another goal is to identify what media transferors need to increase their competence when they are promoted to librarian in the future. The results of this study indicate that the process of placing employees in the media transfer unit is in accordance with the job analysis and workload analysis in the unit, where the media transferor has fulfilled the job requirements such as education, rank, knowledge, abilities, and attitudes. In addition, the competence of the media transferor is deemed sufficient to meet the needs, but his competence needs to be further improved when he becomes a librarian in the media transfer unit later. As for what media transferrs need to improve their competence as librarians, they include technical guidance/training for advanced librarians, socialization of librarian activities, benchmarking of work operational standards in the international arena.